Evaluasi Adopsi Inovasi Feed Additive Herbal untuk Ternak Ayam Pedaging - Ayu Intan Sari (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2009)
The purpose of this research is to evaluate technically and economical adoption of herbal feed additive innovation for broiler. This research was conducted from August to October 2008, in the broiler farm at Karanganyar, Sragen, and Boyolali by using research based method of descriptive analysis. The respondents of the research were 34 farmers selected by using purposive convenience sampling. Evaluation technical adoption of herbal feed additive innovation, was analyzes base on the respondent’s answer to questionnaire which draw a process adoption of innovation, consist of the first reason of farmer apply innovation, process receiving innovation and the difficulties and in apply innovation. The result of research shows based on technical evaluation result there differences adoption innovation process on adopter category early and late, it is first reason receive innovation where on early adopter category because on broiler production higher (52,94%), while the first reason for late adopter category in receive innovation because to save production cost (47,06%). The result also shows that early adopter category of farmers (58,82%) not found difficulties in apply innovation feed additive, while in late category adopter (52,94%) . Found difficulties in apply innovation feed additive. Base on economic evaluation value, the income of broilers farm without using feed additive herbal at scale > 8.000 broiler Rp 2.392,18 per broiler, scale 3001– 8.000 broilers Rp 1.910,54 per broiler, and the income at scale < 3000 broilers Rp 1.616,59 per broiler. Income of broilers farm with using feed additive herbal base on scale > 8.000 broilers Rp 2.557,19 per broiler, scale 3001- 8000 broilers Rp 1.767,15 per broiler. The conclusion from this research are different evaluation score technical adoption innovation feed additive herbal at the early and late adopter category, it is on the first reason in receive innovation where the early adopter category because of the broilers productivity higher, while late adopter category in receive innovation because the save the production cost. Base on economic evaluation result, there is increase income received by farmers after using innovation feed additive herbal and more scale broilers farm, so the advantage which get also bigger. Key words:      Technical evaluation, economic evaluation, adoption invation, herbal feed additive